2008
DOI: 10.1016/j.jpainsymman.2007.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Pain and Quality of Life in Hospitalized Patients with Heart Failure

Abstract: The pain experience of patients with heart failure (HF) and its impact on their quality of life (QOL) has not been described in sufficient detail. This study sampled patients hospitalized with HF to describe the prevalence and severity of bodily pain; evaluate differences in bodily pain related to selected demographic and disease-specific characteristics; and evaluate the effect of selected demographic, disease-specific characteristics, bodily pain, and mental health on QOL. Two items from the Medical Outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 42 publications
(26 reference statements)
4
43
0
1
Order By: Relevance
“…For example, patients who have experienced heart failure reported pain to have a significant impact on their QOL. 20 Moreover, patients with COPD and lung cancer reported that chest pain correlated with the QOL domain. 56 Another example of how QOL is affected by pain is shown in a study by Smith et al 57 In a chronic pain group consisting of patients with neuropathic pain, the pain interference score was related to poor health and more disability than in other chronic pain groups.…”
Section: Impact Of Pain On Qol With Copd Controlling For Selected Dementioning
confidence: 99%
See 1 more Smart Citation
“…For example, patients who have experienced heart failure reported pain to have a significant impact on their QOL. 20 Moreover, patients with COPD and lung cancer reported that chest pain correlated with the QOL domain. 56 Another example of how QOL is affected by pain is shown in a study by Smith et al 57 In a chronic pain group consisting of patients with neuropathic pain, the pain interference score was related to poor health and more disability than in other chronic pain groups.…”
Section: Impact Of Pain On Qol With Copd Controlling For Selected Dementioning
confidence: 99%
“…18 Traditionally, pain is understood as a biopsychosocial phenomenon, calling for the investigation of the burden of pain on psychosocial variables. 19 The experience of pain is reported to affect both disease-specific QOL in patients with heart failure 20 and global QOL in patients with burn injuries. 21 Although disease-specific QOL is often explained by the presence of symptoms, global QOL is frequently conceptualized as satisfaction with overall life domains and happiness in life.…”
mentioning
confidence: 99%
“…24,25 An alternative explanation for this finding is that when family members see a loved one in pain, they advocate for care that might involve rehospitalization. Finally, it also may be that more supportive therapies, such as physical therapy and occupational therapy, are indicated for these patients to address their pain, because the decision tree highlights the importance of the number of anticipated therapy visits among patients with severe pain.…”
Section: Discussionmentioning
confidence: 99%
“…Interview and survey studies with patients with advanced HF find that they have physical, psychological, social, spiritual, and informational needs. [28][29][30][31][32][33] These needs are similar to those of patients with advanced cancer; 34 however, patients with HF understand less about their illness, have fewer choices regarding end-of-life care, and have more limited access to palliative care. 35,36 Patients may desire communication that they do not receive: one study found that not one of 20 patients had discussed disease progression or advanced care planning with staff members.…”
Section: Introductionmentioning
confidence: 99%